1987
DOI: 10.1038/ki.1987.242
|View full text |Cite
|
Sign up to set email alerts
|

Site of the action of a synthetic atrial natriuretic peptide evaluated in humans

Abstract: The renal site of the natriuretic effect of human, atrial natriuretic peptide (hANP) was studied using clearance techniques in eight salt-loaded normal volunteers undergoing maximal water diuresis. Lithium was used as a marker of proximal sodium reabsorption. According to a two-way, single blind, crossover design, hANP (Met12-(3-28)-eicosahexapeptide, (2 micrograms/min) or its vehicle (Ve) were infused for two hours, followed by a two-hour recovery period. Blood pressure, heart rate and insulin clearance remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 45 publications
3
23
1
Order By: Relevance
“…Fractional diluting segment reabsorption decreased as well, which is the opposite of the change caused by mineralocorticoid expansion. Such effects of ANF on renal sodium handling have been found previously by others 24 and by ourselves. 21 -n The rise in GFR after ANF was not larger during escape.…”
Section: Discussionsupporting
confidence: 66%
“…Fractional diluting segment reabsorption decreased as well, which is the opposite of the change caused by mineralocorticoid expansion. Such effects of ANF on renal sodium handling have been found previously by others 24 and by ourselves. 21 -n The rise in GFR after ANF was not larger during escape.…”
Section: Discussionsupporting
confidence: 66%
“…An influence by angiotensin II appears unlikely since ANP administration would be expected to suppress rather to enhance renin release (Maack et al, 1985). Moreover, in our study, the subjects were salt-loaded and exhibited a low renin already to start with (Biollaz et al, 1987). Similarly, plasma arginine vasopressin levels were very low (Biollaz et al, 1987) which also renders the participation of this hormone in the stimulated PG biosynthesis unlikely.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, in our study, the subjects were salt-loaded and exhibited a low renin already to start with (Biollaz et al, 1987). Similarly, plasma arginine vasopressin levels were very low (Biollaz et al, 1987) which also renders the participation of this hormone in the stimulated PG biosynthesis unlikely. Another possible factor could be the UFR per se since, in spite of some contradictory results (Scherer & Weber, 1979;Kramer et al, 1981;Fejes-Toth et al, 1983), many authors have reported that the urinary excretion of PGE2 (Walker et al, 1981;Kaojarern et al, 1984;Haylor et al, 1986) and TxB2 (Zipser & Smorlesi, 1984) were positively related to UFR.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…3334 Although documentation of the latter is inconsistent in direct studies, 35 in clearance studies such as the present one ERPF often falls or tends to fall while GFR rises. 24 - 44 Whereas preglomerular vasodilation promotes natriuresis by increasing GFR and peritubular hydrostatic pressure and flow, the postglomerular vasoconstriction might oppose natriuresis by decreasing peritubular pressure and flow. Ca 2+ entry blockade could have specifically pro-moted the dilatory effect of ANF, which is in agreement with data that indicate a preferential afferent arteriolar action of Ca 2+ entry blockers.…”
Section: Discussionmentioning
confidence: 99%